A series of novel NIR fluorescent dyes: Synthesis, theoretical calculations and fluorescence imaging applications in living cells. (February 2016) - Zhang, Ming; Zheng, Shu-ting; Liu, Xiao-jing; Long, Ying; Yang, Bing-qin
Abstract: A series of NIR fluorescent dyes have been synthesized and characterized. These new dyes displayed excellent photo-physical properties including large Stokes shifts, high fluorescence quantum yields, good photo-stability and low cytotoxicity. Significantly, these novel NIR dyes are superior to the traditional rhodamine dyes, displaying strong emission in the NIR region as well as the rhodamine-like ON–OFF fluorescence switching mechanism. In addition, using one of the new dyes as a platform, a novel Hg 2+ fluorescent sensor was constructed which was capable of imaging Hg 2+ in living cells, demonstrating the practical value of these new dyes. Finally, to understand the mechanism of action of the sensors and their enhanced fluorescence properties, we performed quantum chemical calculations with the B3LYP exchange functional employing 6-31G basis. Highlights: Novel NIR dyes displayed excellent photo-physical properties. A fluorescent sensor for Hg 2+ ions was constructed using the dyes as a platform. Calculations support the reaction. Hg 2+ fluorescent sensor was capable of imaging Hg 2+ in living cells.